INFORMATIVE - COMMUNICATION TECHNOLOGIES DURING THE STUDY OF DISCIPLINE «THERAPEUTIC DENTISTRY» AT THE CHAIR OF THERAPEUTIC DENTISTRY IN HIGHER STATE EDUCATIONAL ESTABLISHMENT OF UKRAINE «UKRAINIAN MEDICAL STOMATOLOGICAL ACADEMY» - N.М. Ilenko; N.V. Kotelevska; O.M. Boychenko (Ukrainian Medical Stomatological Academy, 2017)
Long terms of training, a large amount of information and high requirements for professional training of students - modern conditions of the educational process in medical universities. High demands of modern programs for training can't satisfy, relying only on traditional pedagogical methods of teaching. It is necessary to constantly search for new approaches to the organization of training, which are accompanied by modern information technologies. Inform the educational process at the Department of Therapeutic Dentistry of HSEIU "UMSA" computer equipment, TV-, video- and multimedia equipment are widely used. Teachers of the department, using the resources of information and communication technologies (ICT), prepared all the lecture material in the form of multimedia presentations. Office equipment is widely used in practical classes. Students have access to general information of the department (web-page of the department, reference books for students, etc.). Students learn their grades in the electronic journal. Computer testing has been organized, which has a number of advantages - efficiency of results, simultaneous testing of knowledge of a large number of students, significant time savings. The department practices clinical conferences, where students report clinical cases, accompanied by a multimedia presentation. One of the forms of using ICT in the educational process is the participation of teachers and students in on-line conferences (webinars).Improving the quality of students' preparation for successful professional work in the conditions of European competition is impossible without the creation of a modern material and technical and research base that would ensure the learning process at the level of advanced innovative and educational technologies.